Training on Website Creation as a Media for Promotion and Information on Clay Craft Products in Mayong Lor Village, Jepara Regency - Purwaningrum, Jayanti Putri; Zahro, Nafi’ Inayati; Sutono, Sugoro Bhakti (LPPM UIKA Bogor, 2024)
The aim of this training and mentoring activity is to digitize the marketing of clay-based ornament products in Mayong Lor Village through the use of website applications, so that it is hoped that it can expand the reach of product marketing and increase product sales. The implementation methods used in this activity are situation analysis, training, mentoring and evaluation. Participants in this training activity are business owners Kharisma Clay Art. The implementation of this activity is by providing training and assistance to business owners Kharisma Clay Art regarding the importance of digital marketing, website advantages and how to operate the website. The results achieved from the implementation of this training are that business owner Kharisma Clay Art has more insight regarding digital marketing through website applications and is able to apply and utilize his knowledge in everyday life.